Mesospheric momentum flux studies over Fort Collins CO (41N, 105W) - Acott, Phillip Edward, author; She, Chiao Yao, advisor; Krueger, David A., advisor (Colorado State University. Libraries, 2009)
System upgrades to the Colorado State University Sodium Lidar have enabled over 300 hours of night-time gravity wave momentum flux measurements with concurrent 24-hour measurements of the mean and tidal wind and temperature fields of the mesosphere and lower thermosphere (MLT) region of the atmosphere above Fort Collins, CO. Results include the vertical profile of nighttime zonal momentum flux divided by density (MF/ρ), as well as nighttime wind and temperature variances; the results also provide some insight into the accompanying gravity wave-tidal interactions.

Statistics of MF/ρ and wind and temperature variability compare well with another reported long term sodium lidar study, Gardner and Liu (2007). MF/ρ is averaged over the breadth of the study from September 2006 to June 2007 and over altitudes from 85 km to 95 km yielding an average value of -1.1 ±0.2 m2s-2. A comparison is made of nightly averaged MF/ρ values in the winter months and the months nearest the equinox. This is reported as a monthly mean of -2.4 m2s -2 for the winter months and +0.5 m2/s2 for the months nearest to the two equinoxes.

MF/ρ and tidal interaction is examined. There is anti-correlation between the reconstructed tide and smoothed MF/ρ at the middle altitudes in the observation. This anti-correlation develops with a change in altitude from no noticeable anti-correlation at lower altitudes to anti-correlation at higher altitudes, suggesting interaction between the tides and the high phase speed GWs that are generating the MF/ρ. At highest altitudes in this study the anti-correlation relationship evolves to near quadrature, suggesting that the GWs are no longer being filtered by the tides.

Convergence of the MF/ρ appears to be anti-correlated and correlated with the tidal amplitudes depending upon the altitude and the day of the measurement. Where clear anti-correlation between the convergence of flux and diurnal tidal amplitude is observed (e.g. day 343, 2006) the growth of diurnal tidal amplitude is damped, suggesting transference of energy from the tides into the short period GWs. Further work in the characterization of the tidal amplitude and phase relationship with the MF/ρ modulation, with aid from the continuing long-term tidal study, is anticipated.
Keywords: atmospheric dynamics; lidar; mesosphere; momentum flux; sodium spectroscopy; atmospheric sciences; atomic physics